Creating a copyright literacy strategy: A collaboration between library and academic staff - Morrison, Chris (Septentrio Conference Series, 2020)
This presentation reports on the University of Kent’s development of a copyright literacy strategy. This has been developed to raise awareness of copyright amongst staff and students in order to minimise the risk of copyright infringement, as well as prevent copyright being a barrier to innovative teaching and research. This work builds on a multinational research project to assess the copyright literacy of information professionals (Todorova et al, 2017) and further research in the UK to understand copyright literacy within higher education institutions (Morrison & Secker, 2015; Morrison & Secker 2017; Morrison, 2018). The research has found that copyright is a source of anxiety for library staff who are often expected to have a high level of knowledge of copyright issues. This proves challenging when copyright presents a barrier to teaching and research, and there is a need for nuanced conversations about application of copyright exceptions and risk managed approaches (IFLA, 2018). Copyright has also been identified as a key issue at the intersection between information literacy and scholarly communication (ACRL, 2013). This is particularly relevant when advocating for open science and open scholarship such as identifying and using Creative Commons licensed content. The University of Kent copyright literacy strategy will set out a vision for raising awareness of copyright issues (University of Kent, 2019). It is being developed in collaboration between academic, library and other professional services staff and is intended to encourage its staff and students to take a critical yet responsible approach to managing use of copyright material. This presentation will explain the methodology used to consult with relevant stakeholders and address the tensions between different elements of the University. It will outline the key principles and values behind the strategy and report on practical benefits of adopting a strategic approach to copyright literacy.